Analysis of The Influence of Islamic Work Ethic, Leadership Style of The Principal, Motivation towards The Assessment of The Performance of Junior High School Teacher - Pradiptya, Adhi; Rizkiana, Citra; Sugiyanto, Eviatiwi Kusumaningtyas (Management Analysis Journal, 2022)
This study aims to examine the effect of Islamic work ethic, principal's leadership style, motivation on teacher performance at junior high school teacher. The total of 82 respondents as sample selected using purposive random sampling techniques. Data collection method in this study uses questionnaire and processed by SPSS Statictics 24. Data are analysed by multiple linear regression analysis, goodness of fit test, and coefficient of determination. Determination coefficient shows that teacher performance at junior high school teacher isriati Ngaliyan Semarang is 87,2% affected by Islamic work ethic, principal's leadership style, motivation. The rest 12,8% is explained by other variables outside this study. Then, Islamic work ethic, principal's leadership style, motivation have a positive and significant effect on teacher performance at junior high school teacher isriati ngaliyan Semarang either simultaneously or partially. Furthermore, among these three variables, the most dominant effect is Islamic work ethic.